2016
DOI: 10.1002/2016gl067720
|View full text |Cite
|
Sign up to set email alerts
|

The implication of nonradiative energy fluxes dominating Greenland ice sheet exceptional ablation area surface melt in 2012

Abstract: During two exceptionally large July 2012 multiday Greenland ice sheet melt episodes, nonradiative energy fluxes (sensible, latent, rain, and subsurface collectively) dominated the ablation area surface energy budget of the southern and western ice sheet. On average the nonradiative energy fluxes contributed up to 76% of daily melt energy at nine automatic weather station sites in Greenland. Comprising 6% of the ablation period, these powerful melt episodes resulted in 12–15% of the south and west Greenland aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(147 citation statements)
references
References 53 publications
(92 reference statements)
10
135
1
Order By: Relevance
“…Despite extensive cloud cover on DOY 200, daily ablation (0.058 m w.e.) was above the seasonal average (0.049 m w.e./day), with the non-radiative fluxes dominating Q M (57.6%), highlighting the importance of accurate observation or estimation of non-radiative fluxes on glaciers (Fausto et al, 2016).…”
Section: Discussion Energy Balance Observation and Closurementioning
confidence: 99%
“…Despite extensive cloud cover on DOY 200, daily ablation (0.058 m w.e.) was above the seasonal average (0.049 m w.e./day), with the non-radiative fluxes dominating Q M (57.6%), highlighting the importance of accurate observation or estimation of non-radiative fluxes on glaciers (Fausto et al, 2016).…”
Section: Discussion Energy Balance Observation and Closurementioning
confidence: 99%
“…The fact that f scale > 1 strongly suggests that additional processes might play a role in enhancing surface ablation, e.g. underestimation of modelled sensible heat flux from warm air advection along the GrIS periphery (Noël et al, 2015;Fausto et al, 2016) and uncertainties in cloud representation (Van Tricht et al, 2016). However, as the statistical downscaling approach is not designed to correct for these physical processes, we adopted the empirical approach presented above.…”
Section: Melt and Runoff Adjustmentsmentioning
confidence: 99%
“…These findings are consistent with the recent study of Polashenski et al (2015), which suggested the dry snow albedo decline in C5 data would disappear in C6 after finding no enhancement in light-absorbing impurity concentrations on the interior Greenland Ice Sheet. The declining trends in wet snow and ice surface reflectance and albedo, independently supported by evidence of increased melt activity (Nghiem et al, 2012;Fausto et al, 2016b), remain statistically significant in C6 data, though at lower magnitude. An examination of spatial, wavelength-specific variability in C6 albedo trends indicates several interesting attributes of GrIS albedo decline that may motivate future work to better understand the mechanisms controlling albedo feedbacks on the ice sheet.…”
Section: Future Use Of Modis Datamentioning
confidence: 99%